GeoGram: digital game-based learning tool for improving basic geometric knowledge / Rafizah Kechil, Azlina Mohd Mydin and Wan Anisha Wan Mohammad - Kechil, Rafizah; Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha (Unit Penulisan Dan Penerbitan JSKM, 2022)
Geometry refers to the mathematical study of shapes and space. Students should be able to memories the formulas for the basic shapes and spaces in order to solve geometry problems. Calculation problems will arise due to a lack of knowledge and skills in identifying basic geometry's formula. The goal of the development of GeoGram is to provide students with an edutainment experience in which they can review and improve their knowledge of basic geometry formulas. We designed a game to teach students simple and quick self-learning techniques that they can use at any time. As a game platform, we used a PowerPoint spinning-wheel created by tekhnologic and a tangram created by mathigon. We modify the spinning wheel by adding a task for the player to complete. After spinning the wheel, the player must complete the goal of creating a diagram using the tangram platform by using the provided formula. GeoGram, which includes an edutainment component, will assist students in improving their understanding of geometry formulas. Based on the results of a pre-test and a post-test, students are better able to solve basic geometry applications after being introduced to the GeoGram.